FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEBERHASILAN PEMBANGUNAN DI DESA KEWARAKAN KECAMATAN KALORAN KABUPATEN TEMANGGUNG - Titiek Herawati; Dwi Joko Siswanto; Untung Widagdo; Jarwono; Marjitulastri; Sermatutar David Torkis Eden. H; Sermatutar Fauzan Arif Pratama (PPM Sdirjianbang Akademi Militer, 2024)
The research entitled factors that influence the success of development in the village of Sanahakan Kaloran District, Temanggung Regency. The success of Sanahakan village in carrying out development so that it can improve the welfare of its people who were once famous for their economic limitations. Therefore, the problems to be answered in this study are 1) How is the implementation of development carried out in kwarakan village, Kaloran District, Temangggung Regency?, 2) What is the development implementation strategy in Sanahakan village, Kaloran District, Temanggung Regency. and ) what are the factors that affect the success of the implementation of development in the village of Sanahakan, Kaloran District, Temanggung Regency. The theory used in this study is the theory of village development based on experts and applicable regulations. Meanwhile, the method used is descriptive qualitative method with data collection techniques through observation, interview, and documentation.with informants from the village head, the community and the sanity Village apparatus, purposive snowball sampling was carried out. From the results of the study showed the conclusion that first, the implementation of development in the village of sanity is carried out in accordance with Law No. 6 on the village and regulation of the Minister of Home Affairs No. 114 of 2014. The weakness of this is the finding of various difficulties in understanding and explaining it at a practical level, especially for village governments and communities, so that there are still many differences in views of village officials in understanding a regulation, so that in its implementation there are variations between one village and another. Second, the strategy implemented in the development of sanity village is the creation of spatial planning, empowerment of village-owned enterprises (BUMDes), improvement of human resources (HR), IT and effective communication between institutions. Third, the factors that influence the success of development in Sanity village are human resources (HR) factors,namely the competence of the village head to lead and communicate with various parties and move various existing village institutions so that the village vision to realize a prosperous, religious and cultured society is achieved.